Answer: x=-2 y=2
Step-by-step explanation:
I decided that isolating the y value of the second equation is the best way to start solving.
I divide 3 from both sides to get y= (4-x)/3. With this, I can substitute into the first equation. 4x+3(4-x)/3)=-2.
The multiplying the 3 by the denominator three cancels each other out to make:
4x+4-x=-2.
We subtract 4 on both sides and then subtract x from 4x.
We end up with 3x=-6. Then, we divide both sides by 3.
x=-2.
Now we substitute this into the second equation to solve.
3y=4-(-2)
This becomes 3y=4+2 which is 3y=6
We divide both sides by 3 to get y=2
We end up with x=-2 and y=2.
I hope you learned something :)
Answer:
Step-by-step explanation:
x-intercept: Set y = 0 and solve for x:
0 = mx + b, or mx = -b, or x = -b/m. x-intercept is then (-b/m, 0)
y-intercept: Set x = 0 and solve for y: y = m(0) + b, or y = b. y-intercept is then
(0, b).
Answer:
Step-by-step explanation:
The question is not displaying correctly.
4x·3x = 12x²
Answer:
-9
-6
-4
-3
0
Step-by-step explanation:
hope this helps!